Kebijakan Pengembangan Destinasi Wisata di Kabupaten Wakatobi - Ferlin; Ahmad; La Ode Samsul Barani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of the study was to analise the Tourism Destination Development Policy in Wakatobi Regency. Thesis. Postgraduate Master of Economics Study Program. Halu Oleo University. Supervised by Ahmad and La Ode Samsul Barani.. The result showed that the tourist destinations development policy contained in Regional Regulation Number 04 0f 2017 concerning the Regional Tourism Master Plan of Wakatobi Regency 2016-2025, trouhgt article 49, article 50, article 51, article 52, and article 55 Paragraph 2 states that there are 20 location of Regency Tourism Destination and 7 Regional Tourism Strategic Areas where all the development of each destination area is developed in accordance with its potential, and suppoted by a strategy for developing facilities and infrastructure such as increasing the availability of clean water, increasing the capacity of electrical energy availability, developing telecommunications, stations, improving, waste facilities and infrastructure, improving, wastewater management installations, developing distater mitigation facilities and infrastructure, developing higher education institutions, institutional strengthening facilities and SMK Tourism facilitie, developing tourism health facilities, developing and organizing traditional markets as well as touristattractions. However, the implementation of development needs to be improved such as accessibility, especially in air transport, which currently still disconnected.